Pengelolaan Limbah Infeksius Rumah Tangga pada masa Pandemi COVID-19 - Astry Axmalia; Rendi Ariyanto Sinanto (STIKes Hang Tuah Pekanbaru, 2021)
Handling infectious waste is a major global concern for public health and the environment if improperly hands. Personal protective equipment used masks, gloves are the main contribution to the volume of waste.Â The purpose of this literature study is to discuss ways of handling infectious waste, household at the time of a pandemic COVID-19. The method used is a literature review. Literature in the form of national journals published from 2020 until 2021. The collection of literature using google scholar and http://garuda.ristekbrin.go.id/ database with the keywords